2012
DOI: 10.1111/j.1551-2916.2012.05168.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinkering Reactions During Firing of Recyclable Concrete

Abstract: Thermal transformations occurring during firing of recyclable concrete and hydrated Portland cement paste were monitored quantitatively by in situ and ex situ X‐ray diffraction, thermal analysis, and clinker microscopy. Reactions below 1150°C were dominated by either the decarbonation of calcium carbonates of the limestone aggregate fraction in the recyclable concrete or the low temperature decomposition of cement hydrates of the cement paste. Continued heating of the cement paste showed a rapid and extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Preliminary studies have shown that the properties of the eventually regenerated clinker and cement were comparable to reference cements of similar composition [32,35]. The clinkering reactions during firing of Completely Recyclable Concrete were studied in detail earlier [36].…”
Section: Introductionmentioning
confidence: 98%
“…Preliminary studies have shown that the properties of the eventually regenerated clinker and cement were comparable to reference cements of similar composition [32,35]. The clinkering reactions during firing of Completely Recyclable Concrete were studied in detail earlier [36].…”
Section: Introductionmentioning
confidence: 98%
“…A slight difference occurred between TG/DSC data and XRD analysis, but this relates mostly to the different heating/cooling processes followed and not the analytical techniques; as reported also elsewhere (Snellings et al, 2012), it may be that the crystallisation was improved by soaking time, whereas the carbonation was promoted by air cooling.…”
Section: Thermal Analysis Of the Raw Mealsmentioning
confidence: 83%
“…For both samples three measurements were done and the average was considered. In order to better understand the phenomena which occurred between 900 C and 1350 C the procedure proposed elsewhere (Snellings et al, 2012) was followed. Pellets of OPC and OPC14 were heated at 900 C, 1050 C, 1200 C, 1350 C and 1450 C in a static air furnace (bottom loading furnace).…”
Section: Determination Of the Firing Conditions For Clinkersmentioning
confidence: 99%
“…The diffraction peak of C 4 A 3 $ is generally weakened and the characteristic peak of C 3 S are almost not observed with the increasing burning temperatures. It is probably related to the decomposition of C 4 A 3 $ at temperature higher than 1350°C [27,28] which provides an unfavorable condition for the formation of C 3 S. In general, the intensity of diffractive peak is related to the content and crystallinity of phase [29]. Therefore, this suggests that excessive the A/F molar ratio not facilitates the formation of C 3 S and the coexistence of C 4 A 3 $ and C 3 S. Thus, it can be drawn that the composition and content of liquid phase have the significantly effect on the formation of clinker mineral.…”
Section: Resultsmentioning
confidence: 99%